Supply Chain Management in Agricultural Industry - Fenave Zutsara (Newinera Publisher, 2021)
The study discusses Supply Chain Management in Agricultural Industry. Supply Chain Management (SCM) involves the management of supply chain members, who are divided into two categories: main members (consumers) and supporting members (businesses). More effective cost reductions may assist a corporation in achieving its profit objectives more quickly and efficiently than boosting sales efforts. Supply chain management attempts to control (manage) the growth in demand as rapidly as possible since consumers are increasingly expecting the fulfillment of requests as quickly as possible, even when the demand is unexpected and the product in question is not a typical one (customize).